Proposed interior design of Matahati Fashionista Boutique Muslimah at Lot 2A & 2B Lorong Lahat Mines 2, Bandar Lahat Mines, 31500 Ipoh, Perak Darul Ridzuan for Matahati Fashionista Boutique Muslimah Sdn.Bhd / Suzila Selamat - Selamat, Suzila (Faculty of Architecture, Planning and Surveying, 2012)
This project is proposed interior design of Matahati Fashionista Boutique Muslimah at existing two storey shoplot 2B at Lorong Lahat Mines 2, Bandar Lahat, 31500 Ipoh, Perak Darul Ridzuan for Matahati Fashionista Boutique Muslimah Sdn.Bhd. The total area of the building is 6000 square feet. It was divided into first floor and and second floor. Ipoh is located within the state of Perak, which is in the northern part of Peninsular Malaysia. Such as Melaka, Ipoh is also rich with historical buildings from the British Colonial era such as the Railway Station, the Town Hall and the Court House. Economically, the city's growth stagnated following the collapse in tin prices in the 1970s, so a very large proportion of the historical buildings still exist and functional. The location is very strategic because this it is locate nearby to Ipoh town and Aeon Pengkalan, the biggest shopping mall in Perak. The focus of this study is to analyze and to understand the interior design elements in Muslimah boutique retail. This study will carry on one to get two types of data involved such as a primary and secondary data. For the primary data, researcher get the data by doing four types of research such as on-site observation, on-site measurement, interview with the expert and to get perception and opinion the customer by ask some question to customers who came to the boutique. As for the secondary data, researcher gets the data from by reading the related books, unpublished thesis, articles, journal, newspaper and research on internet.